Modified current collector and preparation method thereof, positive plate and negative-electrode-free sodium ion battery
By forming a modified layer containing aluminum oxide, solid electrolyte and artificial SEI film on an aluminum metal three-dimensional substrate, the problems of energy density and cycle life of sodium ion batteries are solved, and higher energy density and longer cycle life are achieved, while enhancing the safety performance of the battery.
Patent Information
- Application Number
- CN202411799574.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-09
AI Technical Summary
While increasing the energy density of existing sodium ion batteries, there is a risk of short circuit due to fierce growth of sodium dendrites, and the negative electrode current collector modification method is limited, resulting in an increase in the internal resistance of the battery and a short cycle life.
A modified layer containing aluminum oxide, solid electrolyte sodium titanium phosphate and artificial SEI film is formed on an aluminum metal three-dimensional substrate. Through hydrothermal reaction and calcination steps, a modified current collector is formed, which reduces the amount of electrolyte injection, reduces dendrites' growth, and enhances the safety performance of the battery.
It realizes that while ensuring the safety performance of the battery, the energy density and cycle life of the sodium ion battery are improved, the growth of dendrites is reduced, and the safety performance of the battery is enhanced.
Smart Images

Figure CN119601668A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a modified current collector and a preparation method thereof, a positive electrode sheet and a sodium ion battery without a negative electrode. Background Art
[0002] Sodium-ion batteries are expected to become an alternative to lithium batteries due to their readily available raw materials, low price and excellent performance. The positive electrode of sodium-ion batteries mainly includes layered oxide materials, Prussian blue analogue materials, polyanion materials, etc.; the negative electrode of sodium-ion batteries mainly includes hard carbon and soft carbon; the electrolyte of sodium-ion batteries mainly uses esters and ethers as solvents, and Na + It is prepared by metal salt (such as sodium fluoride salt, sodium borate salt and perchlorate) electrolyte and various additives (such as film-forming, flame retardant and overcharge protection). Although sodium ion batteries have the advantages of good low-temperature performance, low cost, high safety and long cycle life, their energy density is still lower than that of lithium ion batteries. Therefore, how to improve the energy density of sodium ion batteries while ensuring the safety performance of the battery is a technical problem that needs to be solved urgently.
[0003] At present, the anode-free sodium metal battery, which is widely studied, has more violent growth of sodium dendrites at higher energy density, which poses a risk of rapid short circuit of the battery, which will seriously hinder the application of sodium ion batteries. Among them, the anode current collector is a key component in the battery. The most common modification is to coat the surface of the aluminum foil with a conductive agent, but it will inevitably introduce a binder and increase the thickness of the current collector, thereby increasing the internal resistance of the battery.
[0004] In summary, there is an urgent need to develop a modification process for the negative electrode current collector to improve the energy density and cycle life of sodium-ion batteries while ensuring battery safety performance.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The purpose of the present invention is to provide a modified current collector and a preparation method thereof, a positive electrode sheet and a negative electrode-free sodium ion battery, aiming to improve the energy density and cycle life of the sodium ion battery while ensuring the safety performance of the battery.
[0007] The present invention is achieved in that:
[0008] In a first aspect, the present invention provides a modified current collector, comprising an aluminum metal three-dimensional substrate, and a modified layer containing aluminum oxide, a solid electrolyte and an artificial SEI film is formed on the surface of the aluminum metal three-dimensional substrate;
[0009] Wherein, the solid electrolyte includes sodium aluminum titanium phosphate;
[0010] The artificial SEI film includes sodium carbonate and sodium fluoride.
[0011] In an optional embodiment, the molar ratio of sodium aluminum titanium phosphate, sodium carbonate and sodium fluoride is 1:(0.1-0.2):(0.1-0.2);
[0012] And / or, the mass proportion of the modified layer in the modified current collector is 5%-20%;
[0013] And / or, the aluminum metal three-dimensional substrate is foamed aluminum or an aluminum mesh.
[0014] In a second aspect, the present invention provides a method for preparing the modified current collector of the aforementioned embodiment, comprising: forming a modified layer containing aluminum oxide, a solid electrolyte and an artificial SEI film on an aluminum metal three-dimensional substrate.
[0015] In an optional embodiment, it includes:
[0016] Pre-oxidation treatment is performed on the aluminum metal three-dimensional substrate to form an aluminum oxide layer on the surface;
[0017] mixing sodium hydrogen phosphate, phosphoric acid, sodium carbonate, sodium fluoride, a hydrolysis inhibitor and water to obtain a reaction solution;
[0018] The reaction solution and the organic titanium source solution are mixed to obtain a modified solution, and the modified solution is hydrothermally reacted with an aluminum metal three-dimensional substrate having an aluminum oxide layer, followed by calcination.
[0019] In an optional embodiment, the process of preparing the reaction solution includes: mixing sodium hydrogen phosphate, phosphoric acid, a complexing agent, sodium carbonate, sodium fluoride and water to obtain a first mixed solution, and mixing the first mixed solution with a hydrolysis inhibitor;
[0020] The molar ratio of sodium hydrogen phosphate, phosphoric acid, complexing agent, sodium carbonate and sodium fluoride is regulated to be (2-4): (7-14): (0.1-0.2): (0.1-0.2): (0.1-0.2); the volume ratio of the first mixed solution and the hydrolysis inhibitor is 1: (2.5-3.5);
[0021] And / or, the sodium hydrogen phosphate salt is selected from at least one of sodium dihydrogen phosphate and sodium monohydrogen phosphate;
[0022] and / or, the hydrolysis inhibitor is selected from at least one of acetic acid, hydrochloric acid, sulfuric acid and nitric acid;
[0023] And / or, the complexing agent is citric acid.
[0024] In an optional embodiment, the organic titanium source solution is obtained by mixing an organic titanium source and an alcohol solvent, the concentration of the organic titanium source solution is 5 mol / L-10 mol / L, the volume ratio of the hydrolysis inhibitor and the organic titanium source is controlled to be 1:(0.8-1.2), and the molar ratio of the amount of water used to prepare the reaction solution to the organic titanium source is (0.45-0.55):1;
[0025] And / or, the organic titanium source is tetrabutyl titanate.
[0026] In an optional embodiment, the hydrothermal reaction temperature is 120°C-200°C, and the hydrothermal reaction time is 6h-12h;
[0027] And / or, the volume of the modifying liquid corresponding to each gram of the aluminum metal three-dimensional substrate having the aluminum oxide layer is 50 mL-150 mL;
[0028] and / or, controlling the calcination temperature to 500° C.-650° C. and the calcination time to 4 h-6 h;
[0029] and / or, after calcination, annealing for 3h-6h;
[0030] And / or, calcination is performed under an inert atmosphere.
[0031] In an optional embodiment, the pre-oxidation treatment is a heat treatment in an oxygen-containing atmosphere, the treatment temperature is controlled to be 200° C.-500° C., and the treatment time is 1 h-2 h; the mass proportion of aluminum oxide in the pre-oxidized current collector obtained after the pre-oxidation treatment is 5%-20%;
[0032] and / or, before the pre-oxidation treatment, the aluminum metal three-dimensional substrate is subjected to surface treatment to remove a surface oxide layer;
[0033] Preferably, the surface treatment comprises first cleaning with an organic solvent and water, and then cleaning with an inorganic acid solution and water.
[0034] In a third aspect, the present invention provides a positive electrode sheet, comprising any modified current collector in the aforementioned embodiment or a modified current collector prepared by any preparation method in the aforementioned embodiment;
[0035] Preferably, the modified current collector is coated with a positive electrode active material layer, and the positive electrode active material in the positive electrode active material layer is at least one selected from the group consisting of polyanion materials, layered oxides and Prussian blue analogs.
[0036] In a fourth aspect, the present invention provides a negative electrode-free sodium ion battery, comprising the sodium ion battery positive electrode of the aforementioned embodiment.
[0037] The present invention has the following beneficial effects: the present invention in-situ grows aluminum oxide and solid electrolyte sodium aluminum titanium phosphate on an aluminum metal three-dimensional substrate, which can provide a faster ion conduction rate, reduce the amount of electrolyte injection, reduce the growth of dendrites, and increase the safety performance of the battery. The solid electrolyte (sodium aluminum titanium phosphate) and the artificial SEI membrane (sodium carbonate / sodium fluoride) are formed on the surface of the three-dimensional current collector, which is conducive to the internal deposition of sodium metal on the three-dimensional substrate, and can prevent the growth of sodium dendrites on the surface of the current collector to prevent puncturing the diaphragm. The solid electrolyte, artificial SEI membrane and negative electrode metal-free battery are used together, so the effect of reducing costs, extending cycle life, and improving battery capacity density and safety is produced. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0039] Figure 1 This is an element distribution diagram of the modified current collector prepared in Example 1; the figure shows the characterization of P, O, Ti, Na, Al and F elements respectively;
[0040] Figure 2 The C element distribution diagram of the modified current collector prepared in Example 1;
[0041] Figure 3 This is a morphology diagram of the modified current collector prepared in Example 1;
[0042] Figure 4 This is the element ratio distribution diagram of the modified current collector prepared in Example 1. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0044] Technical terms:
[0045] Dendrite: Dendrites are crystals that develop in a typical multi-branched tree-like form. Dendrite growth is very common and can be illustrated by snowflake formations and frost patterns on windows.
[0046] The embodiment of the present invention provides a method for preparing a modified current collector, comprising: forming a modified layer containing aluminum oxide, a solid electrolyte and an artificial SEI film on an aluminum metal three-dimensional substrate, the steps being as follows:
[0047] S1. Surface treatment
[0048] Before the pre-oxidation treatment, the aluminum metal three-dimensional substrate is surface treated to remove the surface oxide layer.
[0049] In some embodiments, the aluminum metal three-dimensional substrate may be commercially available foamed aluminum or aluminum mesh, which can better support the solid electrolyte and the artificial SEI film.
[0050] In some embodiments, the surface treatment includes first cleaning with an organic solvent and water to remove surface impurities; then cleaning with an inorganic acid solution to remove the original uneven oxide layer on the surface of the aluminum metal three-dimensional substrate, and then washing with pure water for multiple times to remove the surface acid solution. The type of organic solvent is not limited, and can be acetone, etc.; the inorganic acid solution can be dilute hydrochloric acid, etc.
[0051] S2. Pre-oxidation treatment
[0052] The aluminum metal three-dimensional substrate is pre-oxidized to form a dense and uniform aluminum oxide layer on the surface.
[0053] In some embodiments, the pre-oxidation treatment is performed in an oxygen-containing atmosphere, the treatment temperature is controlled to be 200°C-500°C, the treatment time is 1h-2h, and the surface of the aluminum metal three-dimensional substrate is uniformly oxidized, and a dense and uniform oxide layer Al is formed on the surface. 2 O 3 The mass proportion of aluminum oxide in the pre-oxidized current collector obtained after the pre-oxidation treatment is 5%-20%, such as 5%, 10%, 15%, 20%, etc.
[0054] Specifically, the pre-oxidation treatment can be carried out in a tube furnace, and the oxygen-containing atmosphere can be pure O 2 The temperature of the pre-oxidation treatment may be 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, etc., and the treatment time may be 1.0h, 1.3h, 1.5h, 1.8h, 2.0h, etc.
[0055] S3. Hydrothermal reaction
[0056] Sodium hydrogen phosphate, phosphoric acid, sodium carbonate, sodium fluoride, a hydrolysis inhibitor and water are mixed to obtain a reaction solution; the reaction solution is mixed with an organic titanium source solution to obtain a modified solution, and the modified solution is hydrothermally reacted with an aluminum metal three-dimensional substrate having an aluminum oxide layer. During the reaction, due to the hydrolysis of tetrabutyl titanate, a modified solution can be formed on the aluminum substrate. 2 O3 Sodium aluminum titanium phosphate is grown in situ on the seed layer; when the water is consumed, the sodium carbonate and sodium fluoride dissolved in the water will precipitate on the surface of the three-dimensional substrate to form an artificial SEI film, which will be further strengthened after subsequent calcination.
[0057] In some embodiments, the sodium hydrogen phosphate salt is selected from at least one of sodium dihydrogen phosphate and sodium monohydrogen phosphate, and the sodium hydrogen phosphate salt can be any one or more of the above; the hydrolysis inhibitor is selected from at least one of acetic acid, hydrochloric acid, sulfuric acid and nitric acid, and can be any one or more of the above, which can delay the strong hydrolysis of tetrabutyl titanate. The complexing agent can be citric acid, and the addition of the complexing agent is conducive to regulating the deposition process and forming a dense and uniform modified layer.
[0058] The molar ratio of each component on the modified layer in the product can be further regulated by precisely controlling the amount of each raw material. The process of preparing the reaction solution includes: mixing sodium hydrogen phosphate salt, phosphoric acid, complexing agent, sodium carbonate, sodium fluoride and water to obtain a first mixed solution, and mixing the first mixed solution with a hydrolysis inhibitor; regulating the molar ratio of sodium hydrogen phosphate salt, phosphoric acid, complexing agent, sodium carbonate and sodium fluoride to be (2-4): (7-14): (0.1-0.2): (0.1-0.2): (0.1-0.2), such as 2:7:0.1:0.1:0.1, 3:10:0.15:0.15:0.15, 4:14:0.2:0.2:0.2, etc.; the volume ratio of the first mixed solution to the hydrolysis inhibitor is 1: (2.5-3.5). The dosage of each raw material is preferably within the above range, and the concentration and dosage of the organic titanium source solution are coordinated so that each component on the modified layer in the product meets the preset requirements, further improving the cycle performance and energy density of the battery.
[0059] Specifically, the volume ratio of the first mixed liquid to the hydrolysis inhibitor may be 1:2.5, 1:2.8, 1:3.0, 1:3.2, 1:3.5, etc.
[0060] Further, the organic titanium source solution is obtained by mixing an organic titanium source and an alcohol solvent, and the concentration of the organic titanium source solution is 5mol / L-10mol / L (such as 5mol / L, 6mol / L, 7mol / L, 8mol / L, 9mol / L, 10mol / L, etc.), and the volume ratio of the hydrolysis inhibitor and the organic titanium source is controlled to be 1: (0.8-1.2), such as 1: 0.8, 1: 0.9, 1: 1.0, 1: 1.1, 1: 1.2, etc., and the organic titanium source hydrolysis can be better regulated within this ratio range. The organic titanium source can be tetrabutyl titanate, but is not limited thereto. When preparing the reaction solution, the molar ratio of water to the organic titanium source is (0.45-0.55): 1, such as 0.45: 1, 0.48: 1, 0.50: 1, 0.53: 1, 0.55: 1, etc.
[0061] Furthermore, the volume of the modified liquid corresponding to each gram of aluminum metal three-dimensional substrate with an aluminum oxide layer is 50mL-150mL, the hydrothermal reaction temperature is controlled to be 120℃-200℃, and the hydrothermal reaction time is 6h-12h. By adjusting the dosage ratio of the aluminum metal three-dimensional substrate with an aluminum oxide layer and the modified liquid, and adjusting the hydrothermal temperature and time, the proportion of the modified layer in the overall modified current collector is further adjusted to improve the cycle performance and safety performance of the battery.
[0062] Specifically, the volume of the modified liquid corresponding to each gram of aluminum metal three-dimensional substrate with an aluminum oxide layer can be 50 mL, 80 mL, 100 mL, 120 mL, 150 mL, etc.; the hydrothermal reaction can be carried out in a hydrothermal reactor, the hydrothermal reaction temperature can be 120°C, 150°C, 180°C, 200°C, etc., and the hydrothermal time can be 6h, 8h, 10h, 12h, etc.
[0063] S4. Calcination
[0064] After the hydrothermal reaction is completed, the aluminum metal three-dimensional precursor is taken out and transferred to a tubular furnace for calcination. During the hydrothermal reaction, sodium carbonate and sodium fluoride will precipitate on the surface of the three-dimensional substrate to form an artificial SEI film. After calcination, the artificial SEI film can be more firmly bonded.
[0065] In some embodiments, calcination is performed under an inert atmosphere, the calcination temperature is controlled to be 500°C-650°C, and the calcination time is 4h-6h; after calcination, annealing is performed for 3h-6h. By adjusting the calcination conditions, the modified layer formed on the aluminum metal three-dimensional substrate is more firmly bonded, the growth of dendrites is further reduced, and the safety performance of the battery is increased.
[0066] Specifically, the type of inert atmosphere is not limited, and it can be nitrogen, argon, etc.; the calcination temperature can be 500°C, 530°C, 550°C, 580°C, 600°C, 630°C, 650°C, etc.; the calcination time can be 4.0h, 4.5h, 5.0h, 5.5h, 6.0h, etc. Annealing means that after the calcination time meets the requirements, the temperature is lowered in stages, such as the 4h time cooling stage successively experiences 600°C, 500°C, 400°C, 300°C, 200°C, 100°C, and room temperature. Specifically, the annealing time can be 3h, 4h, 5h, 6h, etc.
[0067] In summary, the preparation method of the modified current collector provided in the embodiment of the present invention is to firstly uniformly distribute Al on the surface of the aluminum metal three-dimensional substrate. 2 O 3 The subsequent hydrothermal method can be used to generate aluminum source Al 2 O 3Sodium aluminum titanium phosphate is grown in situ on the basis of the seeds; solid electrolyte sodium aluminum titanium phosphate is grown in situ on the current collector to provide a faster ion conduction rate, thereby reducing the amount of electrolyte injection, reducing the growth of dendrites, and increasing the safety performance of the battery. Due to the hydrolysis of tetrabutyl titanate, sodium carbonate and sodium fluoride dissolved in water will precipitate on the surface of the three-dimensional substrate to form an artificial SEI film, which will be more solid after subsequent calcination. No binder is used in the hydrothermal in situ growth of sodium aluminum titanium phosphate, which is conducive to the uniform deposition of sodium ions.
[0068] An embodiment of the present invention provides a modified current collector, including an aluminum metal three-dimensional substrate, on the surface of which a modified layer containing aluminum oxide, a solid electrolyte and an artificial SEI film is formed; wherein the solid electrolyte includes sodium aluminum titanium phosphate; and the artificial SEI film includes sodium carbonate and sodium fluoride.
[0069] It should be noted that the embodiment of the present invention constructs a solid electrolyte (sodium aluminum titanium phosphate / aluminum oxide) @ artificial SEI film (sodium carbonate / sodium fluoride) @ aluminum metal three-dimensional current collector. Since the solid electrolyte sodium aluminum titanium phosphate and aluminum oxide are in-situ grown on the current collector, a faster ion conduction rate can be provided, thereby reducing the amount of electrolyte injection, reducing the growth of dendrites, and increasing the safety performance of the battery. The formation of the solid electrolyte (sodium aluminum titanium phosphate / aluminum oxide) and the artificial SEI film (sodium carbonate / sodium fluoride) on the surface of the three-dimensional current collector is conducive to the deposition of sodium metal inside the three-dimensional substrate, which can prevent the growth of sodium dendrites on the surface of the current collector to prevent puncturing the diaphragm.
[0070] Further, the molar ratio of sodium aluminum titanium phosphate, sodium carbonate and sodium fluoride is 1: (0.1-0.2): (0.1-0.2), such as 1: 0.10: 0.10, 1: 0.13: 0.13, 1: 0.15: 0.15, 1: 0.18: 0.18, 1: 0.20: 0.20, etc.; the mass proportion of aluminum oxide in the pre-oxidized current collector is 5%-20%, such as 5%, 10%, 15%, 20%, etc.; the mass proportion of the modified layer in the modified current collector is 5%-20%, such as 5%, 10%, 15%, 20%, etc. Through the amount of each component in the modified layer and the mass proportion of the modified layer, the role of the solid electrolyte (sodium aluminum titanium phosphate / aluminum oxide) and the artificial SEI film (sodium carbonate / sodium fluoride) can be better exerted to prevent sodium dendrites from growing on the surface of the current collector to prevent the diaphragm from being punctured, which can improve the safety performance of the battery.
[0071] An embodiment of the present invention provides a positive electrode sheet, including the modified current collector provided by the embodiment of the present invention. The electrochemical performance of the positive electrode can be significantly improved by improving the modified current collector.
[0072] In some embodiments, a positive electrode active material layer is coated on the modified current collector, and the positive electrode active material in the positive electrode active material layer is selected from at least one of a polyanion material, a layered oxide and a Prussian blue analogue. The positive electrode active material can be any one or more of the above. The method for forming the positive electrode active layer can refer to the prior art.
[0073] An embodiment of the present invention also provides a negative electrode-free sodium ion battery, including the above-mentioned sodium ion battery positive electrode. The modified current collector provided by the embodiment of the present invention is used as the positive electrode current collector, which can prevent sodium dendrites from growing on the surface of the current collector to prevent puncturing the diaphragm, thereby improving the safety performance of the battery.
[0074] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0075] Example 1
[0076] This embodiment provides a method for preparing a modified current collector, the steps are as follows:
[0077] (1) Surface treatment
[0078] Commercially available foamed aluminum was used as the aluminum metal three-dimensional substrate, the length, width and height of the foamed aluminum were 100 mm, 50 mm and 0.2 mm respectively, and the porosity was 80%.
[0079] The aluminum metal three-dimensional substrate was cleaned with acetone and pure water in turn to remove surface impurities, and then the original uneven oxide layer on the surface of the aluminum metal three-dimensional substrate was removed by cleaning with dilute hydrochloric acid with a concentration of 0.5 mol / L. Finally, it was washed with pure water for many times and dried for use.
[0080] (2) Pre-oxidation treatment
[0081] The aluminum metal three-dimensional substrate treated in step (1) was placed in a tube furnace and pure O 2 , temperature 350℃, pre-oxidation 1.5h, aluminum metal three-dimensional substrate surface in pure O 2 The surface of the aluminum alloy was uniformly oxidized under the environment of 2 O 3 .
[0082] (3) Hydrothermal reaction
[0083] Tetrabutyl titanate and anhydrous ethanol were mixed and stirred evenly to obtain a solution A with a concentration of 5 mol / L.
[0084] A mixed aqueous solution of sodium dihydrogen phosphate, phosphoric acid, citric acid, sodium carbonate and sodium fluoride is prepared to obtain solution B, wherein the molar ratio of sodium dihydrogen phosphate, phosphoric acid, citric acid, sodium carbonate and sodium fluoride is 2:7:0.1:0.1:0.1, and the tetrabutyl titanate in the first mixed solution is completely reacted by adjusting the amount of water, and the water is also completely consumed (the molar ratio of water to tetrabutyl titanate is 0.5:1).
[0085] Solution B and acetic acid were mixed in a volume ratio of 1:3 to obtain solution C. In the experiment, the volume ratio of acetic acid and tetrabutyl titanate was maintained at 1:1.
[0086] 3 g of pre-oxidized aluminum metal three-dimensional substrate was placed vertically into the hydrothermal reactor, and solution C and solution A were evenly mixed (the volume of the modified liquid obtained after mixing solution C and solution A was 300 mL), and then immediately poured into the reactor. The hydrothermal reaction temperature was 150°C and the hydrothermal reaction time was 10 h.
[0087] (4) Calcination
[0088] After the hydrothermal reaction, the aluminum metal three-dimensional precursor was taken out and transferred to a tube furnace, calcined at 600°C for 5 hours under inert gas (nitrogen) and annealed for 4 hours. After rolling, a solid electrolyte (sodium aluminum titanium phosphate / aluminum oxide)@artificial SEI film (sodium carbonate / sodium fluoride)@aluminum metal three-dimensional current collector was obtained.
[0089] from Figure 1 and Figure 2 It can be seen that the element distribution of P, O, Ti, Na, Al, F and C, it can be seen that sodium aluminum titanium phosphorus, sodium carbonate and sodium fluoride are present. Figure 4 It can be seen that the total content and approximate proportion are evenly distributed for each element. Figure 3 It is a morphology picture, and it can be seen that the surface of the modified current collector is flat and evenly distributed.
[0090] Example 2
[0091] This embodiment provides a method for preparing a modified current collector, the steps are as follows:
[0092] (1) Surface treatment
[0093] Same as Example 1.
[0094] (2) Pre-oxidation treatment
[0095] The aluminum metal three-dimensional substrate treated in step (1) was placed in a tube furnace and pure O 2 , temperature 200℃, pre-oxidation 2.0h, aluminum metal three-dimensional substrate surface in pure O 2 The surface of the aluminum alloy was uniformly oxidized under the environment of 2 O 3.
[0096] (3) Hydrothermal reaction
[0097] Tetrabutyl titanate and anhydrous ethanol were mixed and stirred evenly to obtain a solution A with a concentration of 10 mol / L.
[0098] A mixed aqueous solution of sodium dihydrogen phosphate, phosphoric acid, citric acid, sodium carbonate and sodium fluoride is prepared to obtain solution B, wherein the molar ratio of sodium dihydrogen phosphate, phosphoric acid, citric acid, sodium carbonate and sodium fluoride is 4:14:0.2:0.2:0.2, and the tetrabutyl titanate in the first mixed solution is completely reacted by adjusting the amount of water, and the water is also completely consumed.
[0099] Solution B and acetic acid were mixed in a volume ratio of 1:2.5 to obtain solution C. In the experiment, the volume ratio of acetic acid and tetrabutyl titanate was maintained at 1:0.8.
[0100] 3 g of pre-oxidized aluminum metal three-dimensional substrate was placed vertically into the hydrothermal reactor, and solution C and solution A were mixed evenly (the volume of the modified liquid obtained after mixing solution C and solution A was 300 mL), and then immediately poured into the reactor. The hydrothermal reaction temperature was 120°C and the hydrothermal reaction time was 12 h.
[0101] (4) Calcination
[0102] After the hydrothermal reaction, the aluminum metal three-dimensional precursor was taken out and transferred to a tube furnace, calcined at 500°C for 6 hours under inert gas (nitrogen), and annealed for 6 hours. After rolling, a solid electrolyte (sodium aluminum titanium phosphate / aluminum oxide)@artificial SEI film (sodium carbonate / sodium fluoride)@aluminum metal three-dimensional current collector was obtained.
[0103] Example 3
[0104] This embodiment provides a method for preparing a modified current collector, the steps are as follows:
[0105] (1) Surface treatment
[0106] Same as Example 1.
[0107] (2) Pre-oxidation treatment
[0108] The aluminum metal three-dimensional substrate treated in step (1) was placed in a tube furnace and pure O 2 , temperature 500℃, pre-oxidation 1.0h, aluminum metal three-dimensional substrate surface in pure O 2 The surface of the aluminum alloy was uniformly oxidized under the environment of 2 O 3 .
[0109] (3) Hydrothermal reaction
[0110] Tetrabutyl titanate and anhydrous ethanol were mixed and stirred evenly to obtain a solution A with a concentration of 7.5 mol / L.
[0111] A mixed aqueous solution of sodium dihydrogen phosphate, phosphoric acid, citric acid, sodium carbonate and sodium fluoride is prepared to obtain solution B, wherein the molar ratio of sodium dihydrogen phosphate, phosphoric acid, citric acid, sodium carbonate and sodium fluoride is 3:10.5:0.15:0.15:0.15, and the tetrabutyl titanate in the first mixed solution is completely reacted by adjusting the amount of water, and the water is also completely consumed.
[0112] Solution B and acetic acid were mixed in a volume ratio of 1:3.5 to obtain solution C. In the experiment, the volume ratio of acetic acid and tetrabutyl titanate was maintained at 1:1.2.
[0113] 3 g of pre-oxidized aluminum metal three-dimensional substrate was placed vertically into the hydrothermal reactor, solution C and solution A were mixed evenly (the volume of the modified liquid obtained after mixing solution C and solution A was 300 mL), and then immediately poured into the reactor. The hydrothermal reaction temperature was 200°C and the hydrothermal reaction time was 6 h.
[0114] (4) Calcination
[0115] After the hydrothermal reaction, the aluminum metal three-dimensional precursor was taken out and transferred to a tube furnace, calcined at 650°C for 4 hours under inert gas (nitrogen) and annealed for 3 hours. After rolling, a solid electrolyte (sodium aluminum titanium phosphate / aluminum oxide)@artificial SEI film (sodium carbonate / sodium fluoride)@aluminum metal three-dimensional current collector was obtained.
[0116] Example 4
[0117] The only difference from Example 1 is that the amount of each raw material used in the hydrothermal reaction in step (3) is different, the molar ratio of sodium dihydrogen phosphate, phosphoric acid, citric acid, sodium carbonate and sodium fluoride is 2:7:0.5:0.5:0.5, and the tetrabutyl titanate in the first mixed solution is completely reacted by adjusting the amount of water, and the water is also completely consumed. Solution B and acetic acid are mixed in a volume ratio of 1:3 to obtain solution C, and the volume ratio of acetic acid and tetrabutyl titanate in the experiment is maintained at 1:1.
[0118] Example 5
[0119] The only difference from Example 1 is that the amount of each raw material used in the hydrothermal reaction in step (3) is different, the molar ratio of sodium dihydrogen phosphate, phosphoric acid, citric acid, sodium carbonate and sodium fluoride is 1:3:0.1:0.1:0.1, and the tetrabutyl titanate in the first mixed solution is completely reacted by adjusting the amount of water, and the water is also completely consumed. Solution B and acetic acid are mixed in a volume ratio of 1:3 to obtain solution C, and the volume ratio of acetic acid and tetrabutyl titanate in the experiment is maintained at 1:1.
[0120] Example 6
[0121] The only difference from Example 1 is that the amount of each raw material used in the hydrothermal reaction in step (3) is different, the molar ratio of sodium dihydrogen phosphate, phosphoric acid, citric acid, sodium carbonate and sodium fluoride is 2:7:0.1:0.1:0.1, and the amount of water is adjusted so that the tetrabutyl titanate in the first mixed solution is not completely reacted, and the water is not completely consumed. Solution B and acetic acid are mixed in a volume ratio of 1:3 to obtain solution C, and the volume ratio of acetic acid and tetrabutyl titanate in the experiment is maintained at 1:1.
[0122] Comparative Example 1
[0123] This comparative example provides unmodified aluminum foil as a current collector.
[0124] Comparative Example 2
[0125] This comparative example provides unmodified aluminum foam as a current collector.
[0126] Comparative Example 3
[0127] The only difference from Example 1 is that sodium carbonate and sodium fluoride are not added in step (3), and the amounts of other raw materials remain unchanged.
[0128] Test Example 1
[0129] The energy density and cycle performance of the sodium ion batteries prepared in the test examples and comparative examples are shown in Table 1.
[0130] Test method: The modified current collector prepared in the embodiment or comparative example is used as the positive current collector, and a positive active material layer is coated. The positive active material in the positive active material layer is a layered oxide (NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 ) to obtain the positive electrode; aluminum foil is used as the negative electrode; the separator is a commercial dry PP base film, injected with ester electrolyte, and a soft-pack battery cell is made by lamination process. The composition of the ester electrolyte is as follows: the electrolyte is 1M sodium salt (NaPF 6) +Solvent (Diethylene glycol dimethyl ether).
[0131] Table 1 Electrochemical performance of sodium ion batteries provided in Examples and Comparative Examples
[0132]
[0133]
[0134] It can be seen from Table 1 that the sodium ion battery prepared in the embodiment of the present invention has higher energy density and better cycle performance.
[0135] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A modified current collector, characterized in that: It includes an aluminum metal three-dimensional substrate, and a modified layer containing aluminum oxide, a solid electrolyte and an artificial SEI film is formed on the surface of the aluminum metal three-dimensional substrate; Wherein, the solid electrolyte comprises sodium aluminum titanium phosphate; The artificial SEI film includes sodium carbonate and sodium fluoride.
2. The modified current collector according to claim 1, characterized in that: The molar ratio of sodium aluminum titanium phosphate, sodium carbonate and sodium fluoride is 1:(0.1-0.2):(0.1-0.2); And / or, the mass proportion of the modified layer in the modified current collector is 5%-20%; And / or, the aluminum metal three-dimensional substrate is foamed aluminum or aluminum mesh.
3. A method for preparing the modified current collector according to claim 1 or 2, characterized in that: include: A modified layer containing aluminum oxide, the solid electrolyte and the artificial SEI film is formed on the aluminum metal three-dimensional substrate.
4. The preparation method according to claim 3, characterized in that: include: Pre-oxidation treatment is performed on the aluminum metal three-dimensional substrate to form an aluminum oxide layer on the surface; mixing sodium hydrogen phosphate, phosphoric acid, sodium carbonate, sodium fluoride, a hydrolysis inhibitor and water to obtain a reaction solution; The reaction solution and an organic titanium source solution are mixed to obtain a modified solution, and the modified solution is subjected to a hydrothermal reaction with an aluminum metal three-dimensional substrate having an aluminum oxide layer, followed by calcination.
5. The preparation method according to claim 4, characterized in that: The process of preparing the reaction solution comprises: mixing sodium hydrogen phosphate, phosphoric acid, a complexing agent, sodium carbonate, sodium fluoride and water to obtain a first mixed solution, and mixing the first mixed solution with the hydrolysis inhibitor; The molar ratio of sodium hydrogen phosphate, phosphoric acid, complexing agent, sodium carbonate and sodium fluoride is regulated to be (2-4): (7-14): (0.1-0.2): (0.1-0.2): (0.1-0.2); the volume ratio of the first mixed solution to the hydrolysis inhibitor is 1: (2.5-3.5); And / or, the sodium hydrogen phosphate salt is selected from at least one of sodium dihydrogen phosphate and sodium monohydrogen phosphate; and / or, the hydrolysis inhibitor is selected from at least one of acetic acid, hydrochloric acid, sulfuric acid and nitric acid; And / or, the complexing agent is citric acid.
6. The preparation method according to claim 4 or 5, characterized in that: The organic titanium source solution is obtained by mixing an organic titanium source and an alcohol solvent, the concentration of the organic titanium source solution is 5 mol / L-10 mol / L, the volume ratio of the hydrolysis inhibitor to the organic titanium source is controlled to be 1:(0.8-1.2), and the molar ratio of the amount of water used to prepare the reaction solution to the organic titanium source is (0.45-0.55):1; And / or, the organic titanium source is tetrabutyl titanate.
7. The preparation method according to claim 4, characterized in that: The hydrothermal reaction temperature is 120°C-200°C, and the hydrothermal reaction time is 6h-12h; And / or, the volume of the modified liquid corresponding to each gram of the aluminum metal three-dimensional substrate having an aluminum oxide layer is 50 mL-150 mL; and / or, controlling the calcination temperature to 500° C.-650° C. and the calcination time to 4 h-6 h; and / or, after calcination, annealing for 3h-6h; And / or, calcination is performed under an inert atmosphere.
8. The preparation method according to claim 4, characterized in that: The pre-oxidation treatment is a heat treatment in an oxygen-containing atmosphere, the treatment temperature is controlled to be 200° C.-500° C., and the treatment time is 1 h-2 h; the mass proportion of aluminum oxide in the pre-oxidized current collector obtained after the pre-oxidation treatment is 5%-20%; and / or, before the pre-oxidation treatment, the aluminum metal three-dimensional substrate is subjected to surface treatment to remove a surface oxide layer; Preferably, the surface treatment comprises first cleaning with an organic solvent and water, and then cleaning with an inorganic acid solution and water.
9. A positive electrode sheet, characterized in that: A modified current collector comprising any one of claims 1 to 2 or a modified current collector prepared by the preparation method of any one of claims 3 to 8; Preferably, the modified current collector is coated with a positive electrode active material layer, and the positive electrode active material in the positive electrode active material layer is at least one selected from the group consisting of polyanion materials, layered oxides and Prussian blue analogs.
10. A negative electrode-free sodium ion battery, characterized in that: Including the sodium ion battery positive electrode as described in claim 9.
Citation Information
Patent Citations
Porous collector and preparation method and lithium battery thereof
CN108550859A
Preparation method and application of composite lithium metal negative electrode material
CN111029589A
Composite current collector, preparation method thereof and application of composite current collector in lithium metal battery
CN118472270A
Current collector, secondary battery, battery module, battery pack, and electric device
CN118507733A
Composite current collector, preparation method of composite current collector and lithium battery without negative electrode
CN119029215A
Cited By
Negative-electrode-free sodium ion battery current collector, preparation method and application thereof, and negative-electrode-free sodium ion battery
CN120600830A
Negative electrode-free sodium-ion battery current collector, preparation method and application thereof, and negative electrode-free sodium-ion battery
CN120600830B